THE IMPACT OF WORKLOAD AND JOB SATISFACTION ON BURNOUT AMONG NURSING HEALTH ASSISTANTS IN SAUDI ARABIAN HOSPITALS - Khalid Mulfi Saud Aldhafeeri, Abdul Mohsen Abdul Aziz Fahad Al Dhafeeri, Mshal Mohammed Ramadan Al Enazi, Ghanem Silfiq Duhaysan Aldhafeeri, Bader Husaykan Khadir Alanazi, Nasser Saad Mukhlid AlMutairi, (Chelonian Research Foundation, 2022)
Background: Nursing health assistants play a crucial role in providing patient care in hospitals. However, high workload and low job satisfaction can lead to burnout, which can negatively impact patient care and outcomes. This study aimed to investigate the impact of workload and job satisfaction on burnout among nursing health assistants in Saudi Arabian hospitals. Methods: A cross-sectional study was conducted among 500 nursing health assistants working in six public hospitals in Riyadh, Saudi Arabia. Data were collected using a structured questionnaire that included the Maslach Burnout Inventory, the NASA Task Load Index, and the Job Satisfaction Survey. Multiple linear regression analysis was used to examine the relationship between workload, job satisfaction, and burnout. Results: The majority of nursing health assistants reported high levels of workload (72.4%) and moderate levels of job satisfaction (58.6%). The prevalence of burnout was 45.2%. Workload and job satisfaction were significant predictors of burnout (β = 0.42, p < 0.001; β = -0.38, p < 0.001, respectively). Nursing health assistants with higher workload and lower job satisfaction had higher levels of burnout. Conclusion: Workload and job satisfaction are significant predictors of burnout among nursing health assistants in Saudi Arabian hospitals. Healthcare organizations should implement strategies to reduce workload and improve job satisfaction among nursing health assistants to prevent burnout and improve patient care quality. Keywords: nursing health assistants, workload, job satisfaction, burnout, Saudi Arabia